INSTITUTIONAL REINFORCEMENT OF ALTERNATIVE DISPUTE RESOLUTION (ADR) WITHIN THE INDONESIAN LEGAL FRAMEWORK NAVIGATING PRACTICAL DEMANDS AND JUDICIAL PARADIGM SHIF - Alimal Yusro Siregar; Tamaulina Br. Sembiring (PT. Sinergi Legal Publisher, 2025)
This study examines the implementation and challenges of reorienting the role of judges as mediators in civil cases through the Alternative Dispute Resolution (ADR) mechanism at the Blangkejeren Sharia Court. Within the framework of national civil procedural law reform, the role of judges is no longer limited to deciding cases, but must transform into peace facilitators. This reorientation is normatively reinforced by Supreme Court Regulation Number 1 of 2016, which requires mediation efforts in every civil case before the main examination. However, at the empirical level, implementation at the Blangkejeren Sharia Court shows a striking duality between the relatively high statistical achievements of mediation and the complexity of obstacles that hamper its effectiveness. The limited number of certified mediator judges, limited time due to caseloads, and resistance to the community's litigative culture are crucial inhibiting factors. Through the approaches of legal system theory (Friedman), living law (Ehrlich), and legal objectives (Radbruch), this study critically examines the gap between the asynchronous legal structure and legal culture. The analysis shows that despite progressive regulations, mediation practices are still implemented solely for procedural purposes, rather than as a substantive mechanism that addresses the root values of society. The novelty offered is the idea of locality-based, sharia-based participatory mediation that combines formal legal values with local socio-religious norms. The Blangkejeren Sharia Court, with its Gayo community-based characteristics rich in deliberation, is worthy of being a national prototype for culture-based ADR transformation. Thus, this research not only fills a gap in the literature but also directly encourages concrete reforms to the face of religious courts to make them more humane, effective, and rooted.